Asbestos Exposure and Attitudes Toward Occupational Health - Swimmer, Gene; Luce, Sally (Relations industrielles / Industrial Relations, 1985)
This paper is concerned with the factors affecting the attitudes of workers who manufacture Asbestos products toward occupational health issues.